2013
DOI: 10.1002/jnr.23251
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory acidic pH enhances hydrogen sulfide-induced transient receptor potential ankyrin 1 activation in RIN-14B cells

Abstract: Hydrogen sulfide (H2 S), a toxic volcanic gas, functions as a gaseous physiological and pathophysiological molecule. Recently we have shown that H2 S elicits acute pain through the activation of transient receptor potential ankyrin 1 (TRPA1), which is expressed mainly in primary nociceptive neurons. We also demonstrated enhancement of H2 S-induced TRPA1 activation and pain under inflammatory acidic conditions, but the underlying mechanism has not been elucidated. Here, we attempted to clarify this mechanism by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…30,31 Comparison of four groups of nerve samples Allogeneic nerve has strong immunogenicity before treatment. 32 Studies have shown that the immunogenicity of extracellular matrix components of nerves, such as laminin protein and fibronectin is weak, and even almost negligible, so the immunogenicity of allogeneic nerve mainly reflects on the cell. 33,34 Schwann cells, as the main cell components of the sciatic nerve, has the function of antigen presentation, and can produce cytokines such as IL-1 and interferon g so as to induce an immune rejection response.…”
Section: The Methods Of Preparation Of Acellular Scaffold and Its Advmentioning
confidence: 99%
“…30,31 Comparison of four groups of nerve samples Allogeneic nerve has strong immunogenicity before treatment. 32 Studies have shown that the immunogenicity of extracellular matrix components of nerves, such as laminin protein and fibronectin is weak, and even almost negligible, so the immunogenicity of allogeneic nerve mainly reflects on the cell. 33,34 Schwann cells, as the main cell components of the sciatic nerve, has the function of antigen presentation, and can produce cytokines such as IL-1 and interferon g so as to induce an immune rejection response.…”
Section: The Methods Of Preparation Of Acellular Scaffold and Its Advmentioning
confidence: 99%
“…The current elicited by Na 2 S 3 exhibited an outward rectifying current–voltage relationship similar to that evoked by AITC. In addition, we used RIN-14B, a rat enterochromaffin cell line that expresses TRPA1 constitutively [ 9 , 34 ]. As shown in Figure 6 C, Na 2 S 3 (10 μM) elicited [Ca 2+ ] i increases in RIN-14B cells.…”
Section: Resultsmentioning
confidence: 99%
“…The H 2 S concentration in polysulfide-containing HEPES-buffered solution was measured according to a protocol described previously [ 9 ]. In brief, Na 2 S 3 (10 μM)-containing HEPES-buffered solution (0.5 ml) was added to 10% trichloroacetic acid (0.25 ml), 1% zinc acetate (0.25 ml).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…216 In vitro and in vivo functional studies demonstrated that H 2 S activates TRPA1. 217,218 Furthermore, acidic pH under pathophysiologic conditions potentiates the capacity of H 2 S to activate TRPA1. 217,218 Sulfur mustard SM (mustard gas, SM) has been used as a chemical WMD since World War I and was recently used in the Iran-Iraq war (1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988).…”
Section: Hydrogen Sulfidementioning
confidence: 99%